EKSPLORASI TEKNIK JAPAN SMOCK PADA BUSANA MASQUERADE BALL PARTY - Suci Ramadhani Maulana; Mally Maeliah (Fesyen Perspektif, 2017)
one of the techniques to decorate fabric that has existed since a long time ago is smock which is one of manipulating fabric that is made to beautify a fashion. The term smock comes from english which means shrink. Smock is a technique in sewing skills that transform a fabric into an emerging motif. One type of smock is japan smock. Japan smock is a smock that looks like a bubble. Japan smock became one of the inspirations on the making of masquerade ball party dress. Masquerade ball party is a party where the guest attend the event wearing costumes and masks. Costume is a style of dress that is used to describe the wearer as a special character. Smock is applied to the masquerade ball party dress because of its uniqueness that suitable to be applied to the masquerade ball party dress that has a characteristic.